The energy industry's response to competitive intelligence in green marketing (case study of Qatar) - Farzad Kazemi; Fatemeh Soltani (Journal of Open Innovation: Technology, Market and Complexity, 2024)
Competitive intelligence can be used as a catalyst to guide green marketing strategies as well as to create and maintain competitive advantage. The purpose of this article is to identify and rank the effective factors of competitive intelligence on green marketing and understand the effects of competitive intelligence components on green marketing components. This is a descriptive and applied research that was conducted on a case-by-case basis among the employees of 4 companies that are active in the field of energy industry in Qatar. The research tool is a questionnaire that confirmed the convergent and divergent validity of the two-stage structure. Analysis by PLS software showed that competitive intelligence has a positive effect on green marketing. Also, the ranking of the components was determined completely. The results of this research state that competitive intelligence as a strategic marketing management tool can modify their approaches to differentiate themselves from others and position themselves as industry leaders in sustainability. According to the study background, this research has an important contribution to the existing knowledge in terms of subject and geographical area and provides a suitable insight to the decision makers of this field.